Biomanufacturing of an organic solvent tolerant and thermostable lipase by recombinant E. coli - Nelofer, Rubina (2012)
Lipases are important industrial enzymes due to their versatile properties, especially the thermostable and organic solvent stable lipases. Natural isolates usually produce lipases in small amounts. Therefore, genes from these microbes are cloned into easily cultivating microorganisms like Escherichia coli for hyper production of the target lipase. This study was designed to develop an efficient large scale bioprocess for a thermostable and organic solvent tolerant lipase (Lip 42) from recombinant E.coli BL21. Different production media were first screened for lipase production by E. coli BL21 in shake flask fermentations. Response surface methodology (RSM) and artificial neural network (ANN) were used to optimize the medium composition and culture conditions. The kinetics of Lip 42 production by E. coli BL21 was evaluated using Monod and Luedeking-Piret equations. The effect of dissolved oxygen tension (DOT) level on growth of E. coli BL21 and Lip 42 production was investigated in batch fermentation using 1 L stirred tank bioreactor. Exponential fedbatch fermentation for Lip 42 production was first developed in 1 L stirred tank bioreactor and then scaled up to 10 L and 50 L. Purification of Lip 42 from the culture broth was carried out by strep II affinity chromatography using different scales of AKTA explorer. The highest Lip 42 production was obtained (28.±4.1 IU/mL) in LB broth with the addition of 1% (w/v) glucose. Using Plakett-Burman design, the most significant variables that influenced Lip 42 production by E. coli BL21 were glucose, NaCl,temperature and induction time. The R2 value calculated by RSM showed a good fit, but higher values of absolute average deviation (AAD) and root mean square error (RMSE) were obtained. ANN predicted with better R2, AAD and RMSE values than RSM. The proposed models for Lip 42 production by E. coli BL21 were sufficient to describe the process using a wide range of initial glucose and yeast extract concentrations, where Lip 42 production was found to be growth associated processes. Lip 42 production (73.85 IU/mL) at optimal DOT level (30% saturation) was about 1.5 times higher than that obtained in fermentation with DOT controlled at low level (10% saturation). Antibiotics should be supplied continuously to the culture to maintain the percentage of plasmid bearing cells at higher levels during exponential fed-batch fermentation of Lip 42 by E. coli. Exponential fed-batch fermentation, where the specific growth rate was controlled at 0.1 h-1 by feeding with glucose, was found optimal for growth of E. coli BL21 (30.32 g/L) and Lip 42 production (130.5 IU/mL). Lip 42 from the culture broth of E. coli was successfully purified with optimal DBC conditions using one step strep II tag affinity chromatography at laboratory scale (2 mL column) with almost 65% recovery with comparable results for purification using larger columns (8 mL and 40 mL). Lip 42 can be economically eluted using 0.1 M NaOH instead of using expensive desthiobiotin. The fermentation employing E. coli for Lip 42 production was successfully scaled-up to 50 L stirred tank bioreactor using a constant DOT approach, where DOT level was controlled at 30% saturation. The information and findings obtained from this study are very useful in the designing and the preparation of standard operating procedure (SOP) of Lip 42 production by recombinant E. coli BL21 at industrial scale.